2022
DOI: 10.4103/ijo.ijo_3139_21
|View full text |Cite
|
Sign up to set email alerts
|

Ocular occlusions in two cases of COVID-19

Abstract: In late 2019, we saw the emergence of a new coronavirus, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which rapidly evolved into a global pandemic. We report two cases of ocular vascular occlusion related to coronavirus disease 2019 (COVID-19) disease. The first case is of choroidal artery occlusion, while the second case is of combined central retinal artery and vein occlusion (CRAO and CRVO). We performed a thorough literature search and to the best of our knowledge, neither any of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…The girl we described developed the ocular manifestation very early in the COVID-19 course, in contrast with many other reports, where patients presented CRAO later during the hospitalization or even after the discharge [ 3 , 5 , 8 , 9 ]. Moreover, unlike our report, adult patients with CRAO often presented a severe form of COVID-19, requiring hospitalization and sometimes intensive care unit (ICU) admission [ 3 , 5 , 6 , 9 , 13 ]; in addition, many of these patients had various risk factors for CRAO, being hypertension the most frequently reported [ 3 5 , 7 , 11 , 13 ].…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The girl we described developed the ocular manifestation very early in the COVID-19 course, in contrast with many other reports, where patients presented CRAO later during the hospitalization or even after the discharge [ 3 , 5 , 8 , 9 ]. Moreover, unlike our report, adult patients with CRAO often presented a severe form of COVID-19, requiring hospitalization and sometimes intensive care unit (ICU) admission [ 3 , 5 , 6 , 9 , 13 ]; in addition, many of these patients had various risk factors for CRAO, being hypertension the most frequently reported [ 3 5 , 7 , 11 , 13 ].…”
Section: Discussioncontrasting
confidence: 97%
“…Several non-invasive treatments have been proposed and tried in some adult cases [ 4 , 7 , 8 , 11 , 13 ]; however these strategies are not uniformly supported by the current scientific literature, since there is no evidence of effectiveness [ 15 , 16 , 30 ]. In order to improve retinal oedema, and bearing in mind the known inflammatory and vasculitis tendency of SARS-CoV-2 infection, iv and oral steroids were administered to our patient, nonetheless with poor visual outcome, in accordance to other adult cases in the literature [ 9 , 12 ] and to the known prognosis of CRAO [ 3 , 8 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…To the best of our knowledge, our case is the first report of CRAO in children with SARS-CoV-2 infection. Nevertheless, several cases have been reported in adults, and a combined central retinal artery and vein occlusion has been described in a 20-year-old Indian [ 49 , 50 , 51 ]. In addition, it is known that the SARS-CoV-2 infection prothrombotic effect may also involve the ocular district [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ucar et al [ 29 ] presented a case of central retinal artery occlusion (CRAO) in a patient with no known cardiovascular risk factors. Kulkarni et al [ 30 ] reported one case of choroidal artery occlusion and one case of both central retinal artery and vein occlusion in patients hospitalized for COVID-19 infection. Similarly, Acharya et al [ 31 ] described the case of a 60-year-old man hospitalized in the intensive care unit for severe respiratory disease who experienced CRAO 12 days later.…”
Section: Retinal Findings In Covid-19 Patientsmentioning
confidence: 99%